Hyperthermia and Radiation Therapy in Locoregional Recurrent Breast Cancers: A Systematic Review and Meta-analysis - Datta, Niloy R; Puric, Emsad; Klingbiel, Dirk; Gomez, Silvia; Bodis, Stephan (International journal of radiation oncology, biology, physics, 2016)
To conduct a systematic review and meta-analysis to evaluate the outcome of hyperthermia (HT) and radiation therapy (RT) in locally recurrent breast cancers (LRBCs). A total of 708 abstracts were screened from 8 databases according to the PRISMA guidelines. Single-arm and 2-arm studies, treating LRBCs with HT and RT but without surgery (for local recurrence) or concurrent chemotherapy were considered. The evaluated endpoint was complete response (CR). Thirty-one full text articles, pertaining to 34 studies, were shortlisted for the meta-analysis. Eight were 2-arm (randomized, n=5; nonrandomized, n=3), whereas 26 were single-arm studies. In all, 627 patients were enrolled in 2-arm and 1483 in single-arm studies. Patients were treated with a median of 7 HT sessions, and an average temperature of 42.5°C was attained. Mean RT dose was 38.2 Gy (range, 26-60 Gy). Hyperthermia was most frequently applied after RT. In the 2-arm studies, a CR of 60.2% was achieved with RT + HT versus 38.1% with RT alone (odds ratio 2.64, 95% confidence interval [CI] 1.66-4.18, P<.0001). Risk ratio and risk difference were 1.57 (95% CI 1.25-1.96, P<.0001) and 0.22 (95% CI 0.11-0.33, P<.0001), respectively. In 26 single-arm studies, RT + HT attained a CR of 63.4% (event rate 0.62, 95% CI 0.57-0.66). Moreover, 779 patients had been previously irradiated (696 from single-arm and 83 from 2-arm studies). A CR of 66.6% (event rate 0.64, 95% CI 0.58-0.70) was achieved with HT and reirradiation (mean ± SD dose: 36.7 ± 7.7 Gy). Mean acute and late grade 3/4 toxicities with RT + HT were 14.4% and 5.2%, respectively. Thermoradiation therapy enhances the likelihood of CR rates in LRBCs over RT alone by 22% with minimal acute and late morbidities. For even those previously irradiated, reirradiation with HT provides locoregional control in two-thirds of the patients. Thermoradiation therapy could therefore be considered as an effective and safe palliative treatment option for LRBCs.